The "X-Ray RheumaCoach" software: a novel tool for enhancing the efficacy and accelerating radiological quantification in rheumatoid arthritis. Issue 6 (1st June 2003) - Wick, M; Peloschek, P; Bögl, K; Graninger, W; Smolen, J S; Kainberger, F
Abstract : Background: Precise diagnosis and follow up treatment of rheumatoid arthritis (RA) requires objective quantification, which is still lacking. For this purpose, radiological analyses are considered to be the most appropriate method. Objective: To develop computer assisted quantification software that is particularly applicable to joint scoring in rheumatic disorders. Methods: 3914 radiographs from hands and feet of 190 patients with RA were collected, expertly examined, analysed, and statistically evaluated. Radiographs were quantified using the conventional Larsen score and the "X-Ray RheumaCoach" (XRRC) software. The XRRC is a Java stand alone application which can support and accelerate, but not fully automate, the scoring procedure in RA. The scorer can apply both the Larsen and the Ratingen-Rau scores. Results: Compared with conventional scoring procedures, the XRRC software accelerated quantification time by ~25%. The program, which is now available on the internet free of charge, ran stably and proved to be a consistently valuable tool. Conclusions: Compared with conventional scoring methods, the XRRC software offers several advantages: ( a ) structured data analysis and input that minimises variance by standardisation; ( b ) faster and more precise calculation of sum scores and indices; ( c ) permanent data storing and fast access to the software's database; ( d ) the possibility of cross calculation to other scores; ( e ) "user friendly" technology and a dedicated help program; ( f ) fast access and data transfer through the internet if desired; and ( g ) reliable documentation of results in a specially designed printout.